LITERATURE REVIEW OF THE IMPACT OF DIGITAL ECONOMY ON THE ECONOMIC GROWTH AND THE DEVELOPMENT STRATEGIES IN THE POST-COVID-19 ERA - MATEI CERNĂIANU A. D (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2023)
The digital economy is considered an effective measure to mitigate the negative economic impact of the coronavirus disease 2019 (COVID-19) outbreak. However, few studies have assessed the role of the digital economy on the economic growth of countries along the Belt and Road and the impact of COVID-19 on their digital industries. This study constructs a comprehensive evaluation index system and applies a panel data regression model to empirically analyze the impact of the digital economy on the economic growth of countries along the "Belt and Road" before COVID-19. The main mechanism of action is to promote the modernization of industrial structure, overall planning of employment and adjustment of employment structure. In addition, COVID-19 has boosted the demand of the digital industry in general, and the impact on the demand side is much greater than that on the supply side. Propose a development strategy to bridge the "digital divide" of the countries along the "Belt and Road” and strengthen the role of the digital economy in the post-COVID-19 era on industrial modernization, employment, and trade